Automatic Defense Against Zero-day Polymorphic Worms in Communication Networks - Mohammed, Mohssen (Auerbach Publications, 2013)
Polymorphic worm attacks are considered one of the top threats to Internet security. They can be used to delay networks, steal information, delete information, and launch flooding attacks against servers. This book supplies unprecedented coverage of how to generate automated signatures for unknown polymorphic worms. Describing attack detection approaches and automated signature generation systems, the book details the design of double-honeynet systems and the experimental investigation of these systems. It also discusses experimental implementation of signature-generation algorithms and discusses what we can expect in future developments.